MENCIPTAKAN RASA PERCAYA DIRI DALAM ORGANISASI - Dirlanudin Dirlanudin (NIAGARA Scientific Journal, 2016)
Organizations in the era of fierce competition requires people who have high confidence in large quantities as well as the level of freedom, independence and capacity of high initiative. Confidence as the ability to cope with the basic challenges of life. People in the organization should be ingrained confidence in the ability to learn, make choices, decisions and manage change, so that organizations create a culture of learning in all functions. Leaders and other members should be an example for behavior that supports self-confidence, then spearhead to all functions of the organization. People who have high confidence are more able to make creativity and innovation. Furthermore, innovative creative people tend to be more prepared to take risks with new ideas that counts sharply to overcome the various problems tasks and organizational challenges of the future.